148 Lipid Targeting Post-Stroke—Targeting Who?. (16th March 2021) - Micallef, C; Bingham, K; Barber, J M
Abstract: Introduction: Frailer patients are at high risk of complications from drugs like statins. Other less frail patients may be undertreated. The Treat Stroke to Target trial showed that high risk patients with atherosclerosis and/or ischaemic heart disease (IHD) who were treated to an LDL level of less than 1.8 mmol/L had a 22% relative risk reduction in major cardiovascular events compared to those with a higher target. In our Quality Improvement. Project: We estimated the numbers of post-stroke cases who might safely benefit from a targeted, pharmacist led intensive lipid management program. Methods: 500 consecutive ischaemic stroke cases with a modified Rankin score (mRS) of 0–3 were identified from the Scottish Stroke Care Audit Database. Those discharged to long term care or dead at the time of data collection were excluded. Data collected was age, evidence of atherosclerosis on vascular imaging, co-morbid IHD, LDL at index admission and between 1 month to 1 year post-stroke, anti-lipid treatment at discharge and up to 1 year post-stroke. Atrial fibrillation patients were included if other risk criteria were met. Results: The mean age of the 500 cases was 70. From this group, 297 (60%) met the entry criteria for "Treat to Stroke Target". 190 (64%) cases had LDL checked post-discharge. 87 cases failed to reach the RCP Stroke Guidance of a 40% reduction in LDL Cholesterol. 66 (22%) of cases had LDL >1.8 mmol/L on most recent check and potentially should have been treated to target. Of the 83 cases excluded due to mRS >3 or significant dependency, 70 cases (84%) were discharged on a statin and importantly 34 (48%) of these died within 1 year of their stroke. Conclusions: Based on annual stroke admissions in our health board, around 86–117 high risk patients could benefit from a virtual lipid treatment intensification clinic.